America's tsunami : [videorecording (DVD)] : are we next? (Discovery Channel, 2008)
A team of leading scientists is investigating whether a tsunami like the one that hit Thailand could strike America. The scientists embark on a journey many miles below the ocean's surface, obtaining new data from an ocean ridge taller than the Alps.